Work and Family Variables as Mediators of the Relationship Between Wives' Employment and Husbands' Well-Being - Parasuraman, Saroj; Greenhaus, Jeffrey H.; Rabinowitz, Samuel; Bedeian, Arthur G.; Mossholder, Kevin W. (Academy of Management Journal, 1989)
This study found that husbands of employed women reported slightly lower levels of job satisfaction, marital adjustment, and quality of life than husbands of housewives. Husbands' time commitment to work and satisfaction with childcare were found to mediate the effect of wives' employment on husbands' job satisfaction and marital adjustment, respectively.